"Giant" red and green core/shell quantum dots with high color purity and photostability. (March 2016) - Huang, Bo; Xu, Ruilin; Zhuo, Ningze; Zhang, Lei; Wang, Haibo; Cui, Yiping; Zhang, Jiayu
Abstract: "Giant" red CdSe/CdS and green CdSeS/ZnS core/shell quantum dots (QDs), whose color purity were ∼100% and 91%, respectively, were synthesized, and the color gamut could be more than 120% relative to the NTSC color space for the display utilizing these two kinds of QDs. Time-resolved photoluminescence (PL) measurement showed that the PL dynamics was evolved from tri-exponential decay to bi-exponential type with the increase of the shell thickness, and the PL decay characteristics of these giant QDs did not evidently change under long-term UV irradiation, indicating that the thick shell could isolate the effect of the surface's defects on the exciton's recombination within these QDs. Their high photostability could have an advantage in the application on display and white-light LEDs. Highlights: "Giant" red CdSe/CdS and green CdSeS/ZnS core/shell quantum dots (QDs), whose color purity were ∼100% and 91%, respectively, were synthesized, and the color gamut could be more than 120% relative to the NTSC color space for the display utilizing these two kinds of QDs. The PL decay characteristics of these giant QDs did not evidently change under long-term UV irradiation, indicating that the thick shell could isolate the effect of the surface's defects on the exciton's recombination within these QDs. Their high photostability could have an advantage in the application on display and white-light LEDs.